Urban Agriculture as a Sustainable Development Strategy: Istanbul Yedikule and Ayvansaray Gardens - Zanjeer, Binan; Zülfikar, Halide Candan (İstanbul Üniversitesi, 2025)
The interest in urban agriculture practices is increasing around the world due to growing awareness at both local and global levels of achieving food security and sustainable development in urban areas. In fact, urban agriculture is not a single practice. The integration of ideas, designs, and applications with designers and users can form different practices of urban agriculture, which can be defined as a set of practices based on social practice theory. Therefore, understanding the social and environmental dynamics of urban agriculture, which have led to its integration into the city structure, is crucial. As a result, analyzing and evaluating the planning of urban agriculture practices in major urban cities can contribute to understanding how these practices are integrated into the urban fabric. In this regard, a study was conducted in Istanbul to analyze Yedikule and Ayvansaray Gardens, located in the historical Fatih district. This study aims to evaluate urban agriculture planning in Istanbul and study its impact on sustainable development and the formation of alternative food networks. “Social Practice Theory” was used as an analytical framework to understand how these practices impact the urban environment and how they interact with local communities. This study aims to explore how planned urban agriculture contributes to the UN’s 2030 sustainable development goals, through analyzing the planning process of urban agriculture in both Yedikule and Ayvansaray gardens.
Keywords: Architecture (Other); Mimarlık (Diğer)